SOSIALISASI BAHAYA BAHAN KIMIA OBAT (BKO) DALAM JAMU DAN PELATIHAN MEMBUAT SEDUHAN HERBAL - Hikmawanti, Ni Putu Ermi; Fatmawati, Sofia; Wiyati, Tuti (JURNAL PENGABDIAN FARMASI DAN SAINS, 2024)
Jamu is a traditional medicine that is still popular with Indonesian people. Jamu consists of herbs or medicinal plants that are efficacious for preventing disease and maintaining body health. Generally, herbal medicine can be prepared by the community themselves. However, nowadays, herbal medicine has developed a lot and is packaged in the form of products that are ready to be consumed. Unfortunately, several herbal medicine products were found to contain prohibited medicinal chemicals (BKO). The community needs socialization of the dangers of BKO and training in making herbal infusions that are safe, easy and healthy for the body. Women from PKK RT 06 RW 05 Malaka Sari are the targets for this activity. The success achievements of the activities were evaluated with a pre-post-test by filling out a questionnaire. In the future, knowledge regarding the safe selection and method of consuming herbal medicine can be applied in the family to maintain body health and preserve the consumption of herbal medicine as Indonesia's cultural heritage.